Dr Jerzy Teofil Szews (1925–2016) nauczyciel akademicki, biografista, badacz dziejów oświaty i wychowania Pomorza Gdańskiego - Żerko, Józef (Biuletyn Historii Wychowania, 2016)
Jerzy Teofil Szews, Ph.D. (1925-2016): a university professor, a biographer, a historian studying education and upbringing in Gdansk Pomerania Jerzy Teofil Szews, Ph.D., was born in Gniezno in 1925. After studies at the Poznań University he worked as a teacher in secondary pedagogical schools in Szklarska Poreba, Lebork, and Wejherowo. Following his academic degree of Doctor of Philosophy in 1967 from the Pedagogical University in Gdansk, he was a professor at the Pedagogical University and the University of Gdansk. He was an eminent biographer, a researcher of ‘the unknown history’ concerning Germanisation of the Polish youth in West Prussia’s secondary schools. He also studied the history of the Philomath Society (a secret Polish student organization operating in the early 19th century in Vilnius under Russian occupation), the beginnings of the secret scouting movement in the Pomerania-upon-Vistula Region (an area south of Gdansk, including Bydgoszcz and Torun), and the history of education and upbringing in Gdansk Pomerania. He wrote 11 books and hundreds of articles.